FACTORS INFLUENCING JUNIOR HIGH SCHOOL STUDENTS' NUMERACY SKILLS IN SOLVING ELECTRICITY COST PROBLEMS - Syaiful Hamzah Nasution; Al Jupri; Abdul Halim Abdullah; Bambang Avip Priatna Martadiputra; Elvandri Yogi Pratama (Universitas Muhammadiyah Metro, 2026)
To support the SDGs, teachers can integrate numeracy problems based on real-life contexts, such as electricity costs. This study aims to describe junior high school students' numeracy skills in solving such problems and to identify the influencing factors. The participants were 152 eighth-grade students selected through purposive sampling, all of whom had mastered the prerequisite material. Data collection was conducted through students' written responses and interviews with selected students. The findings revealed that students' numeracy skills remain low, with a mean score of 32.57, falling into the requiring special intervention category. The contributing factors include unfamiliarity with numeracy problems, difficulties in comprehending contexts, tables, and stimuli, a lack of knowledge of appropriate mathematical tools, weak foundational numeracy skills, errors in data interpretation while reading, infrequent provision of numeracy problems by teachers, and students' anxiety when engaging with numeracy tasks. This study concludes that students' difficulties stem from limited contextual understanding and an inability to apply mathematical concepts appropriately. The implications underscore the need for teachers to provide more frequent exposure to contextual numeracy problems, incorporate explicit instruction on table reading and stimulus interpretation, and implement anxiety-reduction strategies within mathematics classrooms. Untuk mendukung SDGs, guru dapat mengintegrasikan soal-soal numerasi berdasarkan konteks kehidupan nyata, seperti biaya listrik. Penelitian ini bertujuan mendeskripsikan kemampuan numerasi siswa sekolah menengah pertama dalam menyelesaikan soal-soal tersebut serta mengidentifikasi faktor-faktor yang memengaruhinya. Partisipan penelitian adalah 152 siswa kelas VIII yang dipilih melalui teknik purposive sampling, yang seluruhnya telah menguasai materi prasyarat. Pengumpulan data dilakukan melalui jawaban tertulis siswa dan wawancara dengan siswa terpilih. Temuan penelitian mengungkapkan bahwa kemampuan numerasi siswa masih rendah, dengan rerata skor 32,57 yang termasuk dalam kategori intervensi khusus. Faktor-faktor yang berkontribusi meliputi ketidakakrabans dengan soal numerasi, kesulitan dalam memahami konteks, tabel, dan stimulus, kurangnya pengetahuan tentang alat matematika yang tepat, lemahnya keterampilan numerasi dasar, kesalahan dalam menafsirkan data saat membaca, jarangnya pemberian soal numerasi oleh guru, serta kecemasan siswa ketika mengerjakan tugas numerasi. Penelitian ini menyimpulkan bahwa kesulitan siswa bersumber dari pemahaman konteks yang terbatas dan ketidakmampuan dalam menerapkan konsep matematika secara tepat. Implikasi dari temuan ini menekankan perlunya guru memberikan paparan yang lebih sering terhadap soal-soal numerasi kontekstual, mengintegrasikan pengajaran eksplisit tentang membaca tabel dan menafsirkan stimulus, serta menerapkan strategi pengurangan kecemasan di dalam kelas matematika.